A load balanced and energy efficient underwater clustering protocol for UWSN - Xinbin LI; Mengling GAO; Lei YAN (Dianxin kexue)
Focused on the low energy efficiency and short lifetime of underwater wireless sensor network（UWSN）,a load balanced and energy efficient underwater clustering（LBEEUC）protocol for UWSN was proposed.For cluster head settings,due to the consideration of load balanced,the proportion of cluster heads based on experience-load was set.The area with high experience-load could obtain more cluster heads than other areas to process data forwarding.And then,for intra-cluster communication,some relay nodes were set to save energy of long range data transmission between cluster head and nodes.Relay nodes also could be used to eliminate redundant information by advance data fusion.Finally,for inter-cluster routing,Q-learning algorithm was used to implement optimal path planning based on the criterion of least energy consuming.The simulation results demonstrate that the LBEEUC protocol can efficiently improve the energy utilization,prolong the network lifetime and balance the energy consumption of the network.